Gestão da inovação no processo de desenvolvimento de software: o caso de empresas de software do arranjo produtivo local de tecnologia da informação de Goiânia - GO - Corsatto, Cássia Aparecida (Universidade Federal de São Carlos, 2010)
The aims of this projetc involves to study the innovation management context , the way then occurs and identify, at the small bussiness which are localizated in the APL de TI de Goiânia GO, making a link with concepts and theorical studies about the innovation management matter, competitiviness and sustainable development presents in the literature and practices application thereof. Will be analyzed the question about innovation development and its implementation on software development process, as well as it are used like a competitive strategy. This research will be conducted with qualitative and quantitative investigation, bibliographic research and exploratory/descriptive research. It was interviewing managers and employers of this enterprises looking for identifying the best pratices about innovation management at this business. Thus, it was mapped, in defined universe, choose for sampling and selected previously criteria, small businesses that present themselves as innovators enterprises in the Information Techinology activety, localizated at APL de TI de Goiânia GO. It was observed three items: people, process and products and the matters which be able to stimulate learning and knowledge in the innovative companies. The results obtained by means bibliographics search, Field search, using another studies about the APL´s costumers and also observing the management innovation in the enterprises wich yours sustainability strategies allowed us to draw a profile of management innovation within these firms of the requirements and this research make a innovation management profile in this organization, observing the innovation rules subscribed at the 3ªth Edition OSLO GUIDE and understand the innovation management impact in the studied APL.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Gestão da inovação; Sustentabilidade; Arranjo produtivo local; Tecnologia da informação; Innovation management; Sustainability; Local productive arrangement; Information technology; CIENCIAS SOCIAIS APLICADAS